The majority of patients with psoriatic arthritis are not eligible for randomised clinical trials. - Runarsdottir, Eydis E; Gunnarsdottir, Anna I; Love, Thorvardur J; Gunnarsson, Petur S; Gudbjornsson, Bjorn (Clinical And Experimental Rheumatology S.A.S, 2019)
To identify the proportion of patients with psoriatic arthritis (PsA) who would meet inclusion criteria of the randomised clinical trials that were performed leading up to registration of the tumour necrosis factor inhibitors (TNFi). Data from 329 patients with PsA were obtained from an Icelandic database, ICEBIO, medical records at the University Hospital of Iceland, and the private out-patient clinic Laeknasetrid Ltd. The patients were classified according to whether they met the inclusion criteria of the clinical trials that were performed ahead of the registration of each respective TNFi. The reasons for exclusion were also explored. 34% of the patients with complete data available met the inclusion criteria. Clinical data in respect to exclusion and inclusion criteria were incomplete for 13% of the cases. The proportion of patients who met the inclusion criteria was highest among those who received adalimumab and etanercept (53%). Patients who received in iximab had the lowest inclusion rate (23%). The main reason why patients did not meet the inclusion criteria was too few swollen and/or tender joints, or in 45% of excluded cases. Our results demonstrate that two thirds of patients with PsA in Iceland who are treated with TNFi would not have qualified for the randomised clinical trials performed leading up to the registration of the medications. Further studies with regards to whether outcomes are different between those who met the inclusion criteria and those who did not remain to be performed. NordForsk